A green low-carbon rust-resistant concrete and preparation method thereof

By using organosiloxane-modified sodium lignin sulfonate, rice husk ash loaded with grape seed extract and waste tea residue extract in reinforced concrete, as well as carbon fixing agent and bentonite-PNIPAM-amine composite adsorbent in reinforced concrete, the problem of rust during carbonization is solved, and an efficient and environmentally friendly rust resistance effect is achieved.

CN119735404APending Publication Date: 2025-04-01CHINA CONSTR WESTERN CONSTR NORTH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411930908.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing reinforced concrete structures lead to a decrease in alkalinity during the carbonization process, destroying the oxide film on the surface of the steel bars, thereby causing rust and damaging the durability of the structure. At the same time, most commonly used rust inhibitors on the market are chemical synthetic substances, which are costly and not environmentally friendly.

Method used

A green low-carbon rust-resisting concrete is used to form a dense protective film by adding organosiloxane modified sodium lignin sulfonate and rice husk ash loaded with grape seed extract and waste tea residue extract, as well as carbon fixing agents polyethyleneimine and bentonite-PNIPAM-amine composite adsorbent to form a dense protective film to slow or prevent corrosion reactions.

Benefits of technology

It significantly improves the corrosion resistance of steel bars, reduces the risk of steel bars, extends the service life of the structure, and achieves a more environmentally friendly and economical rust resistance effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210269660000121
    Figure BDA0005210269660000121
Patent Text Reader

Abstract

The present application relates to the field of building materials, and specifically discloses green low-carbon rust-resistant concrete and a preparation method thereof, comprising the following raw materials: cement, coarse aggregate, fine aggregate, mineral admixture, rust inhibitor, carbon fixer, additive and water; wherein the rust inhibitor is selected from organic siloxane-modified sodium lignin sulfonate and rice husk ash loaded with green extracts, wherein the green extracts include grape seed extract and waste tea residue extract; the carbon fixer is selected from polyethyleneimine; the preparation method thereof comprises the following steps: S1, after mixing the coarse aggregate and the fine aggregate, cement, mineral admixture and carbon fixer are added, and a primary mixture is obtained by mixing; S2, after mixing the additive and water, the rust inhibitor is added, and then the primary mixture is added and stirred to obtain green low-carbon rust-resistant concrete. The present application has the characteristics of being able to significantly improve the corrosion resistance of steel bars while being more environmentally friendly and green.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of building materials, and more specifically, to a green, low-carbon, rust-resistant concrete and a preparation method thereof. Background Art

[0002] Steel bars can increase the tensile strength and bending strength of concrete. Reinforced concrete structures have become the most common building structures in industry and civil use. The steel bars buried in concrete will form an oxide film on the surface of the steel bars due to the large amount of alkaline substances in the concrete. The pores of the concrete are filled with saturated Ca(OH)2 solution, and the surface of the steel bars will undergo initial electrochemical corrosion. The corrosion products form a dense covering on the surface of the steel bars, namely Fe2O3 and Fe3O4. This covering is called a passivation film. In a highly alkaline environment, that is, when the pH is ≥11.5, it can prevent the steel bars from being further corroded and effectively protect the steel bars. However, carbon dioxide or other acidic gases in the atmosphere penetrate into the voids, neutralizing the concrete and reducing the alkalinity, causing concrete carbonization.

[0003] Concrete carbonation refers to the carbonation phenomenon of concrete during use, which is a kind of chemical corrosion suffered by concrete. The process in which carbon dioxide in the air penetrates into the concrete and reacts chemically with its alkaline substances to produce carbonates and water, which reduces the alkalinity of the concrete. This process is called concrete carbonation, also known as neutralization. For plain concrete, carbonation has the effect of improving the durability of concrete, but for reinforced concrete, carbonation will reduce the alkalinity of concrete. When there are microcracks on the surface of the concrete or the protective layer is carbonized to the surface of the steel bar, the oxide film on the surface of the steel bar will be destroyed in the presence of water and air. The steel bar will rust, and the tensile stress generated by the expansion of the corrosion products will exceed the original tensile stress of the concrete, causing the concrete to expand and crack, thereby causing the destruction of the reinforced concrete structure.

[0004] Therefore, the rust prevention of reinforced concrete is of great significance to the durability of reinforced concrete structures. At present, the common methods to prevent steel corrosion are mainly to add preservatives and surface treatment technology. One of the methods is to perform surface treatment on the steel bars, such as galvanizing or coating with anti-corrosion coatings, which can improve the corrosion resistance of the steel bars, but it increases the construction difficulty and cost. Therefore, the most economical and effective method is to add rust inhibitors, which has become one of the most widely used anti-corrosion technologies. However, most of the rust inhibitors on the market are chemical synthetic substances. Although they can effectively delay the corrosion of steel bars, they are costly and not environmentally friendly, which does not conform to the concept of sustainable development. With the enhancement of environmental protection awareness, people are paying more and more attention to the environmental performance of building materials. Therefore, it is of great significance to provide green rust inhibitors, which are more environmentally friendly and have good rust prevention for reinforced concrete and improve its durability. Summary of the invention

[0005] In order to significantly improve the corrosion resistance of steel bars while being more environmentally friendly and economical, the present application provides a green, low-carbon, rust-resistant concrete and a preparation method thereof.

[0006] In the first aspect, the present application provides a green low-carbon rust-resistant concrete, which adopts the following technical solution: A green low-carbon rust-resistant concrete comprises the following raw materials in parts by weight: 100-150 parts of cement, 400-600 parts of coarse aggregate, 160-220 parts of fine aggregate, 50-60 parts of mineral admixture, 8-15 parts of rust inhibitor, 5-15 parts of carbon fixer, 1-3 parts of admixture and 100-150 parts of water; The rust inhibitor is selected from organic silicone modified sodium lignin sulfonate and rice husk ash loaded with green extracts in a mass ratio of 1: (2-3), wherein the green extracts include grape seed extract and waste tea residue extract; and the carbon fixer is selected from polyethyleneimine.

[0007] By adopting the above technical solution, a rust inhibitor and a carbon fixer are added in the present application. The addition of the carbon fixer can absorb carbon dioxide emitted during the concrete production and mixing process, thereby reducing carbon emissions. On the other hand, the carbon fixer in the present application can also absorb carbon dioxide in the later stage, participate in the absorption and reaction of carbon dioxide before calcium hydroxide, and alleviate the carbonization phenomenon caused by the reaction of carbon dioxide in the air with calcium hydroxide in the concrete, thereby reducing the damage to the passivation film formed on the steel bars due to the reduction of alkalinity by carbonization of the concrete, thereby playing a rust inhibitory role. On the other hand, in the present application, organosiloxane-modified sodium lignin sulfonate and rice husk ash loaded with grape seed extract and waste tea residue extract are added, and the functional groups such as sulfonic acid group and hydroxyl group in the organosiloxane-modified sodium lignin sulfonate chemically adsorb with the metal ions on the surface of the steel bar to form a dense protective film, which can effectively isolate the contact between the corrosive medium and the steel bar surface, thereby slowing down or preventing the corrosion reaction and playing a rust-proof role; Grape seed extract and waste tea residue extract contain a variety of flavonoid plant polyphenols, which can form an adsorption layer on the surface of steel bars, thereby playing a rust-inhibiting role. At the same time, the active ingredients therein can change the potential of the surface of the steel bars, making them in a passivated state and reducing the corrosion rate. It was finally found that grape seed extract and waste tea residue extract have a good rust-inhibiting effect on steel bars in the alkaline environment of this application, and are more environmentally friendly. Moreover, the extracts are extracted from grape seeds and waste tea residues, which have a wider source, realize the recycling of waste resources, and are low in cost. In addition, organic siloxane-modified sodium lignin sulfonate is used as a rust inhibitor. Sodium lignin sulfonate is derived from natural lignin compounds and is more environmentally friendly. The modification treatment of organic siloxane improves the stability and durability of the rust inhibitor. Finally, the rust inhibitor in this application has an excellent rust-inhibiting effect and is more green and environmentally friendly.

[0008] Optionally, the organosiloxane-modified sodium lignin sulfonate is prepared by the following method: Sodium lignin sulfonate is dissolved in water, stirred evenly, and then silane coupling agent and PAMAM are added, the pH is adjusted to 5.5-6.5, and the temperature is raised to 60-70°C. Finally, hydroxy silicone oil is added, reacted for 1-2 hours, neutralized, cooled and dried, and organic siloxane-modified sodium lignin sulfonate is obtained.

[0009] By adopting the above technical solution, sodium lignin sulfonate can be adsorbed on the metal surface to form a protective film, reducing the contact between the metal and the corrosive medium. In addition, sodium lignin sulfonate can also form a complex with iron ions through functional groups such as benzene rings and hydroxyl groups, thereby playing a rust-proof role. The hydroxyl group and silicon-oxygen bond in hydroxy silicone oil can form a chemical bond with the metal surface to form a dense protective film, which can further slow down the corrosion of the metal. In addition, sodium lignin sulfonate has good dispersibility and wettability, and can be evenly adsorbed on the metal surface to improve the density of the protective film.

[0010] In the present application, hydroxy silicone oil is used as a modifier, and a silane coupling agent and a polyamide-amine dendrimer polymer PAMAM are used to achieve cross-linking modification of hydroxy silicone oil and sodium lignin sulfonate through the silane coupling agent. Moreover, as a water-soluble macromolecule containing a large number of amino groups, the amino groups of PAMAM form chemical crosslinks with the hydroxyl groups in the hydroxy silicone oil and the sodium lignin sulfonate, and the amino groups in PAMAM can also form chemical bonds with the sulfonic acid groups in the sodium lignin sulfonate. In this way, a cross-linked network between the sodium lignin sulfonate and the hydroxy silicone oil is achieved through the silane coupling agent and PAMAM, thereby enhancing the stability of the cross-linked modified product in an alkaline environment. Moreover, the product formed by such cross-linking contains hydroxy silicone oil groups that form chemical bonds with the surface of the steel bar, and the dispersibility of the sodium lignin sulfonate can enable the modified product to be uniformly adsorbed on the surface of the steel bar, thereby enhancing the stability of the protective film. Moreover, the cross-linking effect of the PAMAM in the present application also improves the compatibility of the hydroxy silicone oil group in the concrete system, further improving the rust-proof effect.

[0011] Optionally, when preparing the organosiloxane-modified sodium lignin sulfonate, the mass ratio of sodium lignin sulfonate to water is 1:(3-5), the mass ratio of sodium lignin sulfonate to hydroxy silicone oil is 1:(0.6-0.8), and the amount of silane coupling agent added is 1-3wt% of the sodium lignin sulfonate, and the amount of PAMAM added is 3-5wt% of the sodium lignin sulfonate.

[0012] By adopting the above technical solution, the final rust inhibitor has a better rust inhibition effect when the above ratio is used.

[0013] Optionally, rice husk ash loaded with green extract is prepared by the following method: 1) Soak the rice husk ash in a sodium hydroxide solution for 20-40 minutes and then dry it to obtain pretreated rice husk ash; 2) After mixing the green extract and water, add the prepared pretreated rice husk ash and hydroxyethyl cellulose, perform ultrasonic treatment, then add a silane coupling agent, mix and stir, and then dry to obtain rice husk ash loaded with the green extract.

[0014] By adopting the above technical scheme, in the present application, rice husk ash is first soaked in an alkaline solution. This, on the one hand, helps to corrode the surface of the rice husk ash and form pores that are beneficial to the loading of the green extract. On the other hand, it makes the rice husk ash more hydrophilic, which helps to load the rice husk ash and improve its compatibility with the concrete system in the later stage. The green extract is then loaded on the rice husk ash. The addition of hydroxyethyl cellulose is soluble in water and has a certain viscosity, which helps the green extract to bond more firmly to the rice husk ash. Then, under the action of the silane coupling agent, a silane film is formed on the surface of the rice husk ash, which can play a certain role in filling the pores. In this way, the corrosion of the green extract in the concrete system is inhibited to a certain extent, and the durability and stability of the rust inhibitor are improved.

[0015] Optionally, in the preparation process of rice husk ash loaded with green extract, the mass concentration of the sodium hydroxide solution in step 1) is 10-20wt%, and the sodium hydroxide solution covers the rice husk ash; In step 2), the mass ratio of green extract to water is 1:(4-6), the amount of pretreated rice husk ash added is 1.5-2.5 times the mass of the green extract, the amount of hydroxyethyl cellulose added is 3-5wt% of the green extract, and the amount of silane coupling agent added is 3-8wt% of the green extract.

[0016] Optionally, a green extract is prepared by: Grape seeds are washed, dried, and then crushed to obtain grape seed powder raw materials; waste tea residues are washed, crushed to obtain tea residue powder raw materials; Then the tea residue powder raw material is soaked in an acid aqueous solution with a pH of 3-5, and then filtered to obtain an extract A and a filter residue; the filter residue is mixed with a grape seed powder raw material to obtain a raw material powder to be processed, and then 60-70% ethanol is used as a solvent to reflux extract the raw material powder to be processed for 2-3 hours to obtain a mixed extract, which is then filtered and mixed with the extract A, concentrated, and dried to obtain a green extract.

[0017] By adopting the above technical scheme, in the present application, the tea residue powder raw material is first subjected to acid extraction in an acid-water solution to extract most of the catechins, gallic acid and other plant polyphenols, and then the filtered residue is mixed with the grape seed raw material and an alcohol extraction method is adopted to extract polyphenols, which are then loaded on rice husk ash and used as a rust inhibitor.

[0018] Optionally, during the preparation of the green extract, the mass ratio of the grape seed powder raw material to the tea residue powder raw material is 1:(2-3), and the amount of the acid aqueous solution added is 6-8 times the mass of the tea residue powder raw material.

[0019] Optionally, a bentonite-PNIPAM-amine composite adsorbent is further added to the carbon fixer, and the added mass ratio of the bentonite-PNIPAM-amine composite adsorbent to polyethyleneimine is 1:(1.5-2).

[0020] By adopting the above technical solution, the present application also adds a bentonite-PNIPAM-amine composite adsorbent as a carbon fixer to cooperate with polyethyleneimine. Polyethyleneimine can efficiently capture carbon dioxide, generate amino accelerated placement and alkyl carbonate, and can form a protective film on the surface of polyethyleneimine, further enhancing its adsorption capacity for carbon dioxide, thereby reducing the chance of carbon dioxide invading the interior of concrete, helping to maintain the alkaline environment inside the concrete, slowing down the carbonization process of the concrete, and helping to maintain the integrity of the passivation film on the surface of the steel bar by reducing the intrusion of carbon dioxide, thereby reducing steel bar corrosion. The risk of rust can be reduced, and the bentonite-PNIPAM-amine composite adsorbent is compounded with bentonite, temperature-sensitive material poly (N-isopropylacrylamide) PNIPAM and amine substances. Bentonite has certain water storage and release functions due to its microporous structure, and PNIPAM, as a temperature-sensitive material, also plays a water storage and release function according to the external temperature environment. When carbon dioxide corrodes, amine compounds react with carbon dioxide and water to form ammonium salts, which can slow down the carbonization of concrete caused by carbon dioxide corrosion, resulting in a decrease in the alkalinity of concrete and damage to the passivation film of the steel bars, thereby playing a rust-resistant role.

[0021] Optionally, the bentonite-PNIPAM-amine composite adsorbent is prepared by the following method: Diethanolamine and water are mixed in a mass ratio of 1:(2-3), and then PNIPAM is added followed by bentonite. The mixture is ultrasonically dispersed for 10-20 minutes and then dried to obtain a bentonite-PNIPAM-amine composite adsorbent. The added mass ratio of bentonite, PNIPAM and diethanolamine is 1:(0.2-0.3):(0.8-1.2).

[0022] By adopting the above technical solution, diethanolamine is used as the amine compound in this year's application, which has a certain ability to react with carbon dioxide. The above ratio is ultimately used to achieve better carbon dioxide adsorption and rust prevention effects.

[0023] Optionally, the mineral admixtures are selected from silica fume, fly ash and tailings in a mass ratio of 1:(2-3):(3-4).

[0024] By adopting the above technical solution, the above mineral admixtures are added to the raw materials to replace part of the cement, thereby improving the performance of concrete and reducing carbon emissions.

[0025] Optionally, the coarse aggregate is crushed stone with a particle size of 5-20 mm and continuous grading, the fine aggregate is machine-made sand with a fineness modulus of 2.6-2.8; and the admixture is polycarboxylate water reducer.

[0026] In the second aspect, the present application provides a method for preparing green low-carbon rust-resistant concrete, which adopts the following technical solution: A method for preparing green low-carbon rust-resistant concrete comprises the following steps: S1. After mixing the coarse aggregate and the fine aggregate, cement, mineral admixture and carbon fixer are added to obtain a primary mixture; S2. After mixing the admixture and water, a rust inhibitor is added, and then the rust inhibitor is added to the primary mixture and stirred to obtain green low-carbon rust-resistant concrete.

[0027] By adopting the above technical solution, the preparation method of the present application is simple and convenient and easy to realize industrialization.

[0028] In summary, this application has the following beneficial effects: 1. In the present application, organic siloxane-modified sodium lignin sulfonate and rice husk ash loaded with grape seed extract and waste tea residue extract are added. Grape seed extract and waste tea residue extract contain a variety of flavonoid plant polyphenols, which can form an adsorption layer on the surface of steel bars, thereby playing a role in rust prevention. At the same time, the active ingredients therein can change the potential of the steel bar surface, making it in a passivated state and reducing the corrosion rate. Finally, it is found that grape seed extract and waste tea residue extract have a good rust prevention effect on steel bars in the alkaline environment of the present application, and are more environmentally friendly. Moreover, the extracts are extracted from grape seeds and waste tea residues, and the sources are more extensive, realizing the recycling of waste resources and low cost. In addition, organic siloxane-modified sodium lignin sulfonate is used as a rust inhibitor. Sodium lignin sulfonate is derived from natural lignin compounds and is more environmentally friendly. The modification treatment of organic siloxane improves the stability and durability of the rust inhibitor. Finally, the rust inhibitor in the present application plays an excellent rust prevention role and is more environmentally friendly. 2 In this application, hydroxy silicone oil is used as a modifier, and a silane coupling agent and PAMAM are used to achieve cross-linking modification of hydroxy silicone oil and sodium lignin sulfonate. Moreover, PAMAM is a water-soluble macromolecule containing a large number of amino groups. Under acidic conditions, its amino groups form chemical crosslinks with the hydroxyl groups in hydroxy silicone oil and sodium lignin sulfonate, and the amino groups in PAMAM can also form chemical bonds with the sulfonic acid groups in sodium lignin sulfonate. In this way, a cross-linking network between sodium lignin sulfonate and hydroxy silicone oil is achieved through silane coupling agents and PAMAM, thereby enhancing the stability of the cross-linked modified product in an alkaline environment. Moreover, the product formed by such cross-linking contains hydroxy silicone oil groups that form chemical bonds with the surface of the steel bar, and the dispersibility of sodium lignin sulfonate can enable the modified product to be uniformly adsorbed on the surface of the steel bar, thereby enhancing the stability of the protective film. Moreover, the cross-linking effect of PAMAM in this application also improves the compatibility of the hydroxy silicone oil group in the concrete system, further improving the rust-proof effect. DETAILED DESCRIPTION

[0029] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0030] In the following examples, cement is selected from: PO42.5 grade ordinary Portland cement; the water reducer is selected from polycarboxylic acid type water reducer; the tailings are selected from gold tailings, which are obtained by crushing, shaping and screening the gold tailings to obtain a particle size of 1-5 mm.

[0031] The following preparation example is an example of the preparation of organosiloxane modified sodium lignin sulfonate: Preparation Example 1 A method for preparing organosiloxane-modified sodium lignin sulfonate comprises the following steps: Sodium lignin sulfonate was dissolved in water, the mass ratio of sodium lignin sulfonate to water was 1:4, and after stirring evenly, silane coupling agent KH-550 and PAMAM were added, the pH was adjusted to 6, and the temperature was raised to 65°C, and finally hydroxy silicone oil was added, the mass ratio of sodium lignin sulfonate to hydroxy silicone oil was 1:0.7, and the reaction was neutralized after 1.5 hours, and the mixture was cooled and dried to obtain organosiloxane modified sodium lignin sulfonate, wherein the amount of silane coupling agent added was 2wt% of the sodium lignin sulfonate, and the amount of PAMAM added was 4wt% of the sodium lignin sulfonate.

[0032] Preparation Example 2 A method for preparing organosiloxane-modified sodium lignin sulfonate comprises the following steps: Sodium lignin sulfonate was dissolved in water, the mass ratio of sodium lignin sulfonate to water was 1:3, and after stirring evenly, silane coupling agent KH-550 and PAMAM were added, the pH was adjusted to 5.5, and the temperature was raised to 60°C, and finally hydroxy silicone oil was added, the mass ratio of sodium lignin sulfonate to hydroxy silicone oil was 1:0.6, and the reaction was neutralized after 2 hours, and the mixture was cooled and dried to obtain organosiloxane modified sodium lignin sulfonate, wherein the amount of silane coupling agent added was 1wt% of the sodium lignin sulfonate, and the amount of PAMAM added was 3wt% of the sodium lignin sulfonate.

[0033] Preparation Example 3 A method for preparing organosiloxane-modified sodium lignin sulfonate comprises the following steps: Sodium lignin sulfonate was dissolved in water, the mass ratio of sodium lignin sulfonate to water was 1:5, and after stirring evenly, silane coupling agent KH-550 and PAMAM were added, the pH was adjusted to 6.5, and the temperature was raised to 70°C, and finally hydroxy silicone oil was added, the mass ratio of sodium lignin sulfonate to hydroxy silicone oil was 1:0.8, and the reaction was neutralized after 1 hour, and the mixture was cooled and dried to obtain organosiloxane modified sodium lignin sulfonate, wherein the amount of silane coupling agent added was 3wt% of the sodium lignin sulfonate, and the amount of PAMAM added was 5wt% of the sodium lignin sulfonate.

[0034] Preparation Example 4 A method for preparing organosiloxane-modified sodium lignin sulfonate is carried out according to the method in Preparation Example 1, except that PAMAM is replaced by silane coupling agent KH-550 in equal amounts.

[0035] The following preparation example is a preparation example of rice husk ash loaded with green extract Preparation Example 5 A method for preparing rice husk ash loaded with green extract comprises the following steps: 1) Firstly, soak the rice husk ash in a sodium hydroxide solution with a mass concentration of 15 wt% for 30 minutes and then dry it to obtain pretreated rice husk ash, wherein the sodium hydroxide solution covers the rice husk ash; 2) preparing green extract, specifically, washing and drying grape seeds, and then crushing and grinding to obtain 80-100 mesh grape seed powder raw material; washing and crushing waste tea residue to obtain 100-120 mesh tea residue powder raw material; The grape seed powder raw material and the tea residue powder raw material are prepared for use, and the mass ratio of the grape seed powder raw material to the tea residue powder raw material is 1:2.5, and then the tea residue powder raw material is soaked in an acid aqueous solution with a pH of 4 for 2.5 hours, and the amount of the acid aqueous solution added is 6-8 times the mass of the tea residue powder raw material, and then filtered to obtain an extract A and a filtration residue; The filtered residue is mixed with the grape seed powder raw material to obtain the raw material powder to be processed, and then a 65% ethanol solution is used as a solvent to perform reverse reflux extraction on the raw material powder to be processed, that is, the material and the solvent are continuously extracted in counter-phase motion, wherein the conveying speed of the raw material powder to be processed is 40 g / min, and the conveying speed of the ethanol solution is 90 mL / min, to obtain a mixed extract, which is then filtered and mixed with extract A, concentrated to be alcohol-free, and dried to obtain a green extract; The green extract and water were mixed in a mass ratio of 1:5, and the prepared pretreated rice husk ash and hydroxyethyl cellulose were added, and ultrasonic treatment was performed for 35 minutes. Then, the silane coupling agent KH-550 was added, and the mixture was mixed and stirred, and the temperature was raised to 50°C. After stirring for 50 minutes, the mixture was cooled and dried to obtain rice husk ash loaded with green extract, wherein the amount of pretreated rice husk ash added was 2 times the mass of the green extract, the amount of hydroxyethyl cellulose added was 4wt% of the green extract, and the amount of silane coupling agent added was 5wt% of the green extract.

[0036] Preparation Example 6 A method for preparing rice husk ash loaded with green extract comprises the following steps: 1) soaking the rice husk ash in a 10 wt% sodium hydroxide solution for 20 min and then drying it to obtain pretreated rice husk ash, wherein the sodium hydroxide solution covers the rice husk ash; 2) preparing green extract, specifically, washing and drying grape seeds, and then crushing and grinding to obtain 80-100 mesh grape seed powder raw material; washing and crushing waste tea residue to obtain 100-120 mesh tea residue powder raw material; The grape seed powder raw material and the tea residue powder raw material are prepared for use, and the mass ratio of the grape seed powder raw material to the tea residue powder raw material is 1:2, and then the tea residue powder raw material is soaked in an acid aqueous solution with a pH of 3-5 for 2 hours, and the amount of the acid aqueous solution added is 6 times the mass of the tea residue powder raw material, and then filtered to obtain an extract A and a filtration residue; The filtered residue is mixed with the grape seed powder raw material to obtain the raw material powder to be processed, and then a 60% ethanol solution is used as a solvent to perform reverse reflux extraction on the raw material powder to be processed, that is, the material and the solvent are continuously extracted in counter-phase motion, wherein the conveying speed of the raw material powder to be processed is 30 g / min, and the conveying speed of the ethanol solution is 80 mL / min, to obtain a mixed extract, which is then filtered and mixed with extract A, concentrated to be alcohol-free, and dried to obtain a green extract; The green extract and water were mixed in a mass ratio of 1:4, and the prepared pretreated rice husk ash and hydroxyethyl cellulose were added, and ultrasonic treatment was performed for 30 minutes. Then, the silane coupling agent KH-550 was added, and the mixture was mixed and stirred, and the temperature was raised to 45°C. After stirring for 60 minutes, the mixture was cooled and dried to obtain rice husk ash loaded with green extract, wherein the amount of pretreated rice husk ash added was 1.5 times the mass of the green extract, the amount of hydroxyethyl cellulose added was 3wt% of the green extract, and the amount of silane coupling agent added was 3wt% of the green extract.

[0037] Preparation Example 7 A method for preparing rice husk ash loaded with green extract comprises the following steps: 1) Firstly, soak the rice husk ash in a sodium hydroxide solution with a mass concentration of 20 wt% for 40 minutes and then dry it to obtain pretreated rice husk ash, wherein the sodium hydroxide solution covers the rice husk ash; 2) preparing green extract, specifically, washing and drying grape seeds, and then crushing and grinding to obtain 80-100 mesh grape seed powder raw material; washing and crushing waste tea residue to obtain 100-120 mesh tea residue powder raw material; The grape seed powder raw material and the tea residue powder raw material are prepared for use, and the mass ratio of the grape seed powder raw material to the tea residue powder raw material is 1:3, and then the tea residue powder raw material is soaked in an acid aqueous solution with a pH of 5 for 3 hours, and the amount of the acid aqueous solution added is 8 times the mass of the tea residue powder raw material, and then filtered to obtain an extract A and a filtration residue; The filtered residue is mixed with the grape seed powder raw material to obtain the raw material powder to be processed, and then a 70% ethanol solution is used as a solvent to perform reverse reflux extraction on the raw material powder to be processed, that is, the material and the solvent are continuously extracted in counter-phase motion, wherein the conveying speed of the raw material powder to be processed is 50 g / min, and the conveying speed of the ethanol solution is 100 mL / min, to obtain a mixed extract, which is then filtered and mixed with extract A, concentrated to be alcohol-free, and dried to obtain a green extract; The green extract and water were mixed in a mass ratio of 1:6, and the prepared pretreated rice husk ash and hydroxyethyl cellulose were added, ultrasonically treated for 40 minutes, and then the silane coupling agent KH-550 was added. After mixing and stirring, the temperature was raised to 55°C, stirred for 40 minutes, and then cooled and dried to obtain rice husk ash loaded with green extract, wherein the amount of pretreated rice husk ash added was 2.5 mass times of the green extract, the amount of hydroxyethyl cellulose added was 5wt% of the green extract, and the amount of silane coupling agent added was 8wt% of the green extract.

[0038] Preparation Example 8 A method for preparing rice husk ash loaded with green extract is according to the method in Preparation Example 5, except that step S1 is not performed.

[0039] Comparative Preparation Example 1 A method for preparing rice husk ash loaded with green extract, according to the method in Preparation Example 5, except that the green extract is grape seed extract.

[0040] Example 1 A method for preparing green low-carbon rust-resistant concrete comprises the following steps: S1. After mixing 500 g of coarse aggregate and 190 g of fine aggregate, 120 g of cement, 100-150 g of mineral admixture and 10 g of carbon fixer were added to obtain a primary mixture; S2. Mix 2g of polycarboxylate water-reducing agent as an admixture with 120g of water, add 12g of rust inhibitor, and then add the primary mixture and stir to obtain green low-carbon rust-resistant concrete.

[0041] Among them, in step S1, the mineral admixtures are silica fume, fly ash and tailings slag in a mass ratio of 1:2.5:3.5, the coarse aggregate is crushed stone with a particle size of 5-20 mm and continuous grading, the fine aggregate is machine-made sand with a fineness modulus of 2.6-2.8, the carbon fixer is polyethyleneimine, and the rust inhibitor is the organosiloxane-modified sodium lignin sulfonate prepared in Preparation Example 1 and the rice husk ash loaded with green extract prepared in Preparation Example 5 in a mass ratio of 1:2.5.

[0042] Example 2 A method for preparing green low-carbon rust-resistant concrete comprises the following steps: S1. After mixing 400 g of coarse aggregate and 160 g of fine aggregate, 100 g of cement, 100 g of mineral admixture and 5 g of carbon fixer were added to obtain a primary mixture; S2. Mix 1g of the admixture polycarboxylate water reducer and 100g of water, add 8g of rust inhibitor, and then add the primary mixture and stir to obtain green low-carbon rust-resistant concrete.

[0043] Among them, in step S1, the mineral admixtures are silica fume, fly ash and tailings slag in a mass ratio of 1:2:3, the coarse aggregate is crushed stone with a particle size of 5-20 mm and continuous grading, the fine aggregate is machine-made sand with a fineness modulus of 2.6-2.8, the carbon fixer is polyethyleneimine, and the rust inhibitor is the organosiloxane-modified sodium lignin sulfonate prepared in Preparation Example 2 and the rice husk ash loaded with green extract prepared in Preparation Example 6 in a mass ratio of 1:2.

[0044] Example 3 A method for preparing green low-carbon rust-resistant concrete comprises the following steps: S1. After mixing 600 g of coarse aggregate and 220 g of fine aggregate, 150 g of cement, 150 g of mineral admixture and 15 g of carbon fixer were added to obtain a primary mixture; S2. Mix 3g of polycarboxylate water-reducing agent and 150g of water, add 15g of rust inhibitor, and then add the primary mixture and stir to obtain green low-carbon rust-resistant concrete.

[0045] Among them, in step S1, the mineral admixtures are silica fume, fly ash and tailings in a mass ratio of 1:3:4, the coarse aggregate is crushed stone with a particle size of 5-20 mm and continuous grading, the fine aggregate is machine-made sand with a fineness modulus of 2.6-2.8, the carbon fixer is polyethyleneimine, and the rust inhibitor is the organosiloxane-modified sodium lignin sulfonate prepared in Preparation Example 3 and the rice husk ash loaded with green extract prepared in Preparation Example 7 in a mass ratio of 1:3.

[0046] Example 4 A method for preparing green low-carbon rust-resistant concrete is carried out according to the method in Example 1, except that the organosiloxane-modified sodium lignin sulfonate is the organosiloxane-modified sodium lignin sulfonate prepared in Preparation Example 4.

[0047] Example 5 A method for preparing green, low-carbon, rust-resistant concrete is carried out according to the method in Example 1, except that the rice husk ash loaded with green extract is the rice husk ash loaded with green extract prepared in Preparation Example 8.

[0048] Example 6 A method for preparing green low-carbon rust-resistant concrete is carried out according to the method in Example 1, except that the carbon fixer is a mixture of bentonite-PNIPAM-amine composite adsorbent and polyethyleneimine in a mass ratio of 1:1.8, wherein the bentonite-PNIPAM-amine composite adsorbent is prepared by the following method: Diethanolamine and water were mixed in a mass ratio of 1:2.5, and then PNIPAM and bentonite were added. After ultrasonic dispersion for 15 minutes, the mixture was dried to obtain a bentonite-PNIPAM-amine composite adsorbent. The added mass ratio of bentonite, PNIPAM and diethanolamine was 1:0.2:1.

[0049] Example 7 A method for preparing green low-carbon rust-resistant concrete is carried out according to the method in Example 1, except that the carbon fixer is a mixture of bentonite-PNIPAM-amine composite adsorbent and polyethyleneimine in a mass ratio of 1:1.5, wherein the bentonite-PNIPAM-amine composite adsorbent is prepared by the following method: Diethanolamine and water were mixed in a mass ratio of 1:2, and then PNIPAM and bentonite were added. After ultrasonic dispersion for 10 minutes, the mixture was dried to obtain a bentonite-PNIPAM-amine composite adsorbent. The added mass ratio of bentonite, PNIPAM and diethanolamine was 1:0.2:0.8.

[0050] Example 8 A method for preparing green low-carbon rust-resistant concrete is carried out according to the method in Example 1, except that the carbon fixer is a mixture of bentonite-PNIPAM-amine composite adsorbent and polyethyleneimine in a mass ratio of 1:2, wherein the bentonite-PNIPAM-amine composite adsorbent is prepared by the following method: Diethanolamine and water were mixed in a mass ratio of 1:3, and then PNIPAM and bentonite were added. After ultrasonic dispersion for 20 minutes, the mixture was dried to obtain a bentonite-PNIPAM-amine composite adsorbent. The added mass ratio of bentonite, PNIPAM and diethanolamine was 1:0.3:1.2.

[0051] Example 9 A method for preparing green low-carbon rust-resistant concrete is carried out according to the method in Example 1, except that a mixture of diethanolamine and polyethyleneimine in a mass ratio of 1:1.8 is selected as the carbon fixer.

[0052] Comparative Example 1 A method for preparing green, low-carbon, rust-resistant concrete is carried out according to the method in Example 1, except that the rust inhibitor is rice husk ash loaded with green extract prepared in Comparative Preparation Example 1.

[0053] Comparative Example 2 A method for preparing green low-carbon rust-resistant concrete is carried out according to the method in Example 1, except that an equal amount of the organosiloxane-modified sodium lignin sulfonate in the rust inhibitor is replaced by sodium lignin sulfonate.

[0054] Comparative Example 3 A method for preparing green low-carbon rust-resistant concrete is carried out according to the method in Example 1, except that no carbon fixer is added to the raw materials.

[0055] Comparative Example 4 A method for preparing green, low-carbon, rust-resistant concrete is carried out according to the method in Example 1, except that the rice husk ash loaded with green extract is replaced with an equal amount of the green extract prepared in Preparation Example 5, and the rice husk ash loading treatment is not performed.

[0056] Comparative Example 5 A method for preparing green and low-carbon rust-resistant concrete is carried out according to the method in Example 1, except that an equal amount of rice husk ash loaded with green extract is replaced by a mixture of green extract and rice husk ash prepared in Preparation Example 5, and the green extract and rice husk ash are directly added in a mass ratio of 1:2.

[0057] Comparative Example 6 A method for preparing green low-carbon rust-resistant concrete is carried out according to the method in Example 1, except that calcium nitrite is used as the rust inhibitor.

[0058] Performance Testing The concrete prepared in the examples and comparative examples of the present application was cast in a mold pre-embedded with steel bars, and the reinforced concrete was cured to prepare the reinforced concrete. Then, the reinforced concrete was subjected to an accelerated carbonization test. The specific parameters were as follows: the carbonization test was carried out in an atmosphere of 80% mass concentration of carbon dioxide, a temperature of 20±2°C, and a humidity of 70±5%. Then, the corrosion current density (μA / cm2) of the reinforced concrete after 7 days of carbonization and the corrosion current density (μA / cm2) of the reinforced concrete after 90 days of carbonization were detected. 2 )(Linear polarization principle method), the test results are shown in Table 1 below.

[0059] In addition, the concrete prepared in the examples of the present application and the comparative examples were subjected to accelerated carbonization tests in accordance with the provisions of GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The carbonization test conditions were: CO2 mass fraction of 20%, temperature of 20±2°C, humidity of 70±5%, and the carbonization depth was measured after 28 days. The test results are shown in Table 1 below.

[0060] Table 1: The greater the corrosion current density, the faster the corrosion rate of the steel bar and the more serious the corrosion degree. Referring to the test results in Table 1 above, the carbonization depth and corrosion degree of the concrete obtained in the embodiment of the present application after the accelerated carbonization test are low. Referring to the test results of Example 1 and Example 4, when the sodium lignin sulfonate is modified by organosiloxane, when hydroxy silicone oil and silane coupling agent are directly used for modification without adding PAMAM, its rust-resistant effect is reduced, especially with the increase of carbonization time, its rust-resistant effect is reduced, and combined with the test results of Example 5, when the rice husk ash in Example 5 is not treated with alkali, its effect is also slightly reduced, especially the rust-resistant effect after long-term carbonization, and alkali treatment can adjust the load and sustained release effect of rice husk ash for green extracts; combined with the test results of Example 1 and Example 6-8, when bentonite-PNIPAM-amine composite adsorbent is also added to the concrete as a carbon fixer, its rust-resistant effect is excellent in the later stage of long-term carbonization, and the carbonization depth is significantly reduced. Referring to the test results of Example 9, when only amine compounds are selected in the rust inhibitor, the effect is limited, especially after long-term carbonization, the rust inhibition effect is limited.

[0061] Combined with the test results of Example 1 and Comparative Example 1, it can be seen that when the waste tea residue extract is not added to the green extract, its rust inhibition effect is reduced, and the waste tea residue extract achieves waste recycling; combined with the test results of Example 1 and Comparative Example 2, when the sodium lignin sulfonate in the rust inhibitor in Comparative Example 2 is added without modification, its rust inhibition effect is significantly reduced, and combined with the test results of Comparative Example 3, when the carbon fixer is not added to the raw material, its short-term and long-term rust inhibition effects are significantly reduced. Referring to the test results of Comparative Example 4, when the green extract is directly added to the rust inhibitor in Comparative Example 4 without loading, its rust inhibition effect after long-term carbonization is reduced. Combined with the test results of Comparative Example 5, when the green extract and rice husk ash are directly physically mixed as raw materials without loading treatment, its rust inhibition effect after long-term carbonization is significantly reduced. Referring to the test results of Comparative Example 6, the rust inhibition effect in this application is close to that of Comparative Example 6, and the rust inhibitor in this application is more environmentally friendly and green.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A green low-carbon rust-resistant concrete, characterized in that: It includes the following raw materials in parts by weight: 100-150 parts of cement, 400-600 parts of coarse aggregate, 160-220 parts of fine aggregate, 50-60 parts of mineral admixture, 8-15 parts of rust inhibitor, 5-15 parts of carbon fixer, 1-3 parts of admixture and 100-150 parts of water; The rust inhibitor is selected from organic silicone modified sodium lignin sulfonate and rice husk ash loaded with green extracts in a mass ratio of 1: (2-3), wherein the green extracts include grape seed extract and waste tea residue extract; the carbon fixer is polyethyleneimine.

2. The green low-carbon rust-resistant concrete according to claim 1, characterized in that: The organosiloxane-modified sodium lignin sulfonate is prepared by the following method: Sodium lignin sulfonate was dissolved in water, stirred evenly, and then silane coupling agent and PAMAM were added. The pH was adjusted to 5.5-6.5, and the temperature was raised to 60-70°C. Finally, hydroxy silicone oil was added, reacted for 1-2 hours, neutralized, cooled and dried, and organic siloxane-modified sodium lignin sulfonate was obtained.

3. The green low-carbon rust-resistant concrete according to claim 2, characterized in that: When preparing the organosiloxane-modified sodium lignin sulfonate, the mass ratio of sodium lignin sulfonate to water is 1: (3-5), the mass ratio of sodium lignin sulfonate to hydroxy silicone oil is 1: (0.6-0.8), and the amount of silane coupling agent added is 1-3wt% of the sodium lignin sulfonate, and the amount of PAMAM added is 3-5wt% of the sodium lignin sulfonate.

4. The green low-carbon rust-resistant concrete according to claim 1, characterized in that: Rice husk ash loaded with green extract was prepared by the following method: 1) Soak the rice husk ash in a sodium hydroxide solution for 20-40 minutes and then dry it to obtain pretreated rice husk ash; 2) After mixing the green extract and water, add the prepared pretreated rice husk ash and hydroxyethyl cellulose, perform ultrasonic treatment, then add the silane coupling agent, mix and stir, and then dry to obtain rice husk ash loaded with the green extract.

5. The green low-carbon rust-resistant concrete according to claim 4, characterized in that: In the preparation process of rice husk ash loaded with green extract, the mass concentration of the sodium hydroxide solution in step 1) is 10-20wt%, and the sodium hydroxide solution covers the rice husk ash; In step 2), the mass ratio of green extract to water is 1:(4-6), the amount of pretreated rice husk ash added is 1.5-2.5 times the mass of the green extract, the amount of hydroxyethyl cellulose added is 3-5wt% of the green extract, and the amount of silane coupling agent added is 3-8wt% of the green extract.

6. The green low-carbon rust-resistant concrete according to claim 1, characterized in that: Green extract is prepared by the following method: Grape seeds are washed, dried, and then crushed to obtain grape seed powder raw materials; waste tea residues are washed, crushed to obtain tea residue powder raw materials; Then, the tea residue powder raw material is soaked in an acid aqueous solution with a pH of 3-5, and then filtered to obtain an extract A and a filter residue; The filtered residue is mixed with the grape seed powder raw material to obtain the raw material powder to be processed, and then 60-70% ethanol is used as a solvent to perform reflux extraction on the raw material powder to obtain a mixed extract, which is then filtered and mixed with extract A, concentrated, and dried to obtain a green extract.

7. The green low-carbon rust-resistant concrete according to claim 6, characterized in that: During the preparation of the green extract, the mass ratio of the grape seed powder raw material to the tea residue powder raw material is 1:(2-3), and the amount of the acid aqueous solution added is 6-8 times the mass of the tea residue powder raw material.

8. The green low-carbon rust-resistant concrete according to claim 1, characterized in that: The mineral admixtures are selected from silica fume, fly ash and tailings in a mass ratio of 1:(2-3):(3-4).

9. The green low-carbon rust-resistant concrete according to claim 1, characterized in that: The coarse aggregate is crushed stone with a particle size of 5-20 mm and continuous grading, the fine aggregate is machine-made sand with a fineness modulus of 2.6-2.8; the admixture is polycarboxylate water reducer.

10. The method for preparing the green low-carbon rust-resistant concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. After mixing the coarse aggregate and the fine aggregate, cement, mineral admixture and carbon fixer are added to obtain a primary mixture; S2. After mixing the admixture and water, add the rust inhibitor, and then add the primary mixture and stir to obtain green low-carbon rust-resistant concrete.

Citation Information

Cited By

  • Light low-temperature foaming mining filling material, preparation method and application

    CN121627345A